Detailed structural analysis of two spliced HSV-1 immediate-early mRNAs. - Rixon, F J (1982)
The structures of two HSV-1 immediate-early mRNAs have been determined by nuclease-digestion procedures using 5' and 3' end-labelled DNA probes. These mRNAs, which map across the junctions between the short unique (US) and short repeat (IRS and TRS) genome regions, have common 5' portions located in IRS and TRS. The 3' portions, which extend into opposite ends of US, and unique. The DNA sequence encoding the common 5' portions largely comprises a 247 base pair (bp) leader region and a single intron of variable size. The variation in intron length is due to different copy numbers of a 22 bp tandem reiteration. A small proportion of the mRNA population is unspliced, but otherwise is identical to the more abundant spliced species.